Driving Sustainability Through AI: A Study on ChatGPT’s Influence on Green Entrepreneurial Processes: https://doi.org/10.55966/assaj.2025.4.1.0112 - Muhammad Muaaz Tahir*; Aamar Ilyas; Rehman ul Hassan; Abu Bakar Waheed; Saud Alam; Wasif Mehmood (`, 2025)
This study examines the influence of ChatGPT adoption on green entrepreneurial behavior (GEB) through the mediating roles of green entrepreneurial self-efficacy (GESE), motivation (GEM), and intention (GEI). Grounded in Social Cognitive Theory, Self-Determination Theory, and the Theory of Planned Behavior, the research proposes a sequential mediation model to explore how AI tools like ChatGPT enhance sustainability-driven entrepreneurial actions. Using a quantitative approach, data were collected from 450 students in Gujranwala, Pakistan, through structured questionnaires. The results, analyzed using SPSS and Hayes’ PROCESS macro, confirmed all 10 direct and 11 indirect hypotheses. Key findings revealed that ChatGPT adoption significantly boosts GESE (β = 0.47, *p* < 0.001), GEM (β = 0.42, *p* < 0.001), and GEI (β = 0.51, *p* < 0.001), with GEI emerging as the strongest predictor of GEB (β = 0.34, *p* < 0.001). Mediation analysis demonstrated full mediation via GEI (β = 0.17, 95% CI [0.10, 0.25]), underscoring the critical role of intention in translating AI usage into sustainable practices. The study contributes to the literature by bridging AI and green entrepreneurship, offering theoretical insights into how technology enhances psychological drivers of eco-friendly ventures. Practical implications include integrating ChatGPT into entrepreneurship training and policymaking to foster sustainable startups. Limitations, such as the cross-sectional design and student sample, suggest future research should explore longitudinal data and diverse entrepreneurial populations. Overall, this study highlights ChatGPT’s transformative potential in advancing green entrepreneurship and achieving sustainability goals. Keywords: ChatGPT; Green Entrepreneurship; Self-efficacy; Motivation; Intention; Sustainable Behavior; AI in Entrepreneurship